Integrative taxonomic reassessment of Aegialitis rotundifolia (Plumbaginaceae) in Thailand based on morphological, anatomical, and palynological evidence - CHATCHAI NGERNSAENGSARUAY; PRANOM CHUMRIANG; PICHET CHANTON; DECHA DUANGNAMON; NITTAYA MIANMIT (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Ngernsaengsaruay C, Chumriang P, Chanton P, Duangnamon D, Mianmit N. 2026. Integrative taxonomic reassessment of Aegialitis rotundifolia (Plumbaginaceae) in Thailand based on morphological, anatomical, and palynological evidences. Biodiversitas 27 (7): d270718. https://doi.org/10.13057/biodiv/d270718. Aegialitis rotundifolia (Plumbaginaceae) is taxonomically revised for Thailand using an integrative approach based on morphology, leaf anatomy, and pollen morphology characteristics. This study clarifies the taxonomic status of Thai populations and designates a lectotype for the species. Leaf anatomical and palynological characters were examined using Light Microscopy (LM) and Scanning Electron Microscopy (SEM). Based on morphological characters, A. rotundifolia is the only Aegialitis species presently recorded from Thailand. Leaves are bifacial and exhibit typical mangrove adaptations, including a thick cuticle, hypodermal cells, abundant salt glands, and sclereids contributing to their coriaceous texture. Salt crystals are commonly present on the leaf surface as a result of secretion and evaporation. Astrosclereids and branched sclereids occur in the mesophyll, providing additional mechanical support. Pollen grains are monads, tricolpate, and large, with scabrate exine sculpturing, and range from spheroidal to subprolate in shape. The species occurs in mangrove and estuarine habitats on heterogeneous sandy-muddy to rocky substrates and exhibits cryptovivipary, with germination occurring while the propagule remains attached to the parent plant. Aegialitis rotundifolia is currently assessed as Near Threatened (NT) at the global level according to the IUCN Red List. This study provides integrative taxonomic evidence supporting the species delimitation and taxonomic identity of A. rotundifolia in Thailand, and supports future systematic and conservation studies of mangrove biodiversity.